Exámen especial a la cartera vencida de la cooperativa de ahorro y crédito Sumak Kawsay ltda, provincia de Cotopaxi cantón Latacunga en el período - Guanoluisa Muso, María Trancito (2016)
In the present research, it made a special exam to due portfolio to the Credit Union “SUMAK KAWSAY LTDA” from January 1st to December 31th 2014; to determine its stability and recovery within the term, knowing its rules, policies and processes in the granting of credits and recovery of all due portfolio. The research was done based on Auditing Standards Generally Accepted which allowed to examine all information on backups, where the validation was determined. The special examination to NPLs establishes a process for making future decisions for the means of approval that there working in the Credit Union, in conducting this research work was collected and analyzed data from a representative sample of all existing partners. The recommendations identified will allow current and future challenges by the application of a systematic and consistent process that will increase the profitability of the Cooperative, what will provide its stability within in the financial sector of the Cotopaxi Province.